Sistem Pembelajaran Pendidikan Agama Islam Perspektif Multidisipliner - Rahmat, Rahmat; Zamroni, M Afif (JoEMS (Journal of Education and Management Studies), 2024)
Teachers are required to be able to design a good and even ideal learning system. And a learning as a system will create the momentum of an ideal teaching and learning process if all components of the system are well organized. The learning component consists of at least 1) teacher, 2) students, 3) facilities and infrastructure, and 4) evaluation. In this case, students who are none other than members of the learning component are directed to be an active central point in driving other components or so-called student center. This means, an indication of ideal learning is when such learning can teach students and or make students aware that learning is the main basic need for them in addition to other needs such as food, clothing, and shelter. Thus this paper tries to analyze a learning system that can encourage students to learn consciously, independently and responsibly. Therefore, the appropriate research method used is descriptive qualitative with multidisciplinary analysis, namely by analyzing the texts of scientific papers such as journals, books -books, scientific articles and the like as well as in-depth analysis based on several disciplines including psychology, economics and information and communication technology sciences. This research produces a module-based learning system with a multidisciplinary study which is very useful in the practice of learning Islamic religious education. Keywords: Module System, PAI, Multidisciplinary Analysis